Feeling Mixed, Ambivalent, and in Flux: The Social Functions of Emotional Complexity for Leaders - Rothman, Naomi B.; Melwani, Shimul (Academy of Management Review, 2017)
We propose that the experience and expression of emotional complexity, including the simultaneous and sequential experience of emotional complexity, can be beneficial for leaders’ ability to lead change. Using the social functions of emotions perspective, we suggest that the primary function of emotional complexity is to increase cognitive flexibility. Specifically, we present a model that explains how, when, and why emotional complexity is functional for leaders at the individual and interpersonal levels of analysis. At the individual level, leaders who experience emotional complexity are more cognitively flexible and, thus, make more adaptive decisions. We further propose that not all leaders will experience such benefits from emotional complexity; individual differences of neuroticism and openness to experience will moderate the leader emotional complexity–cognitive flexibility relationship. Extending our analysis to the interpersonal level, we propose that when followers observe leaders expressing emotional complexity, they will make positive inferences of cognitive flexibility and be empowered to act proactively. We explore a relational factor—the followers’ shared vantage point with their leader—and a situational factor—competing demands as moderators of this relationship. We draw attention to the broader implications of our theorizing for research on leadership and emotions and its practical implications for management.